Flirtation, desire, and cut-glass biscuit barrels: Forms of expertise in Antiques Road Trip. (December 2016) - Smith, Angela; Higgins, Michael
Abstract: This article looks at the development of broadcast talk in those reality TV genres associated with shopping and negotiation, focusing on Antiques Road Trip. In a context in which reality TV has become associated with judgement and rancour, we are concerned with the balance between expertise and ordinariness, and exploring the place of conversational and interactional styles we have come to associate with "sociability" and the maintenance of "face", both in terms of pleasure and spectacle and providing a tactical basis for on-screen negotiation. We argue that these performances differ from conventional discourses of expertise as arbiters of specialist insight and market value, and offer new performances of expertise, based on a tactical mix of professional capital and sociability. Highlights: Antiques Road Trip offers viewers not only a chance to see there are a number of different ways prices can be arrived at. The performance imperatives of broadcast discourse emphasize the performances of flirtation and desire. While these forms of performance are novel in their articulation with expertise, they are commonplace in media more broadly. We find here that the expertise is geared towards popular expertise and the pleasures of interaction.